On collapsible pushdown automata, their graphs and the power of links - Broadbent, C; Christopher Broadbent (2011)
Higher-Order Pushdown Automata (HOPDA) are abstract machines equipped with a nested stacks of stacks... of stacks of stacks. Collapsible pushdown automata (CPDA) enhance these stacks with the addition of ‘links’ emanating from atomic elements to the higher-order stacks below. For trees CPDA are equi-expressive with recursion schemes, which can be viewed as simply-typed λY terms. With vanilla HOPDA, one can only capture schemes satisfying a syntactic constraint called safety. This dissertation begins with some results concerning the signiﬁcance of links in terms of recursion schemes. We introduce a ﬁne-grained notion of safety that allows us to correlate the need for links of a given order with the imposition of safety on variables of a corresponding order. This generalises some joint work with William Blum that shows we can dispense with homogeneous types when characterising safety. We complement this result with a demonstration that homogeneity by itself does not constrain the expressivity of otherwise unrestricted recursion schemes. The main results of the dissertation, however, concern the conﬁguration graphs of CPDA. Whilst the conﬁguration graphs of HOPDA are well understood and have decidable MSO theories (they coincide with the Caucal hierarchy), relatively little is known about the transition graphs of CPDA. It is known that they already have undecidable MSO theories at order-2, but Kartzow recently showed that 2-CPDA graphs are tree automatic and hence ﬁrst-order logic is decidable at order-2. We provide a characterisation of the decidability of ﬁrst-order logic on CPDA graphs in terms of quantiﬁer-alternation and the order of CPDA stacks and the links contained within. Whilst this characterisation is fairly comprehensive, we do leave open the question of decidability for some sub-classes of CPDA. It turns out that decidability can be highly sensitive to the order of links in a stack relative to the order of the stack itself. In addition to some strong and surprising undecidability results, we also develop further Kartzow’s work on 2-CPDA. We introduce preﬁx-rewrite systems for nested-words that characterise the conﬁguration graphs of both 2-CPDA and 2-HOPDA, capturing the power of collapse precisely in terms outside of the language of CPDA. It also formalises and demonstrates the inherent asymmetry of the collapse operation. This generalises the rational preﬁx-rewriting systems characterising conventional pushdown graphs and we believe establishes the 2-CPDA graphs as an interesting and robust class.